531TiPCANOPY-A: A phase III, placebo-controlled study of canakinumab as adjuvant therapy in patients (pts) with surgically resected NSCLC. (24th November 2019) - Cho, B C; Chang, G-C; Kim, Y-C; Geater, S; Saeteng, S; Yang, C-T; Goto, Y; Lu, S; Ardizzoni, A; Barlesi, F; De Marchi, P; Paz-Ares, L; et al.
Abstract: Background: Overexpression of interleukin (IL)-1β has been described in solid tumors, including lung. IL-1β can promote angiogenesis, tumor invasiveness, and induces tumor-associated immunosuppression through myeloid-derived suppressor cell (MDSC) accumulation in tumors. Pre-clinical data has shown that IL-1β inhibition reduced tumor growth, by limiting pro-tumorigenic inflammation and polarization of MDSCs into M1 phenotype. Canakinumab is a human monoclonal antibody with high affinity and specificity for IL-1β. Recently, it was found that canakinumab was associated with a significant and dose-dependent reduction in incidence and mortality from lung cancer based on CANTOS study. Trial design: CANOPY-A (NCT03447769) is a phase III, randomized, double-blind, placebo-controlled study designed to evaluate efficacy and safety of adjuvant canakinumab vs placebo in pts with surgically resected NSCLC. This trial will enroll adult pts, with completely resected (R0) AJCC/UICC v.8 stages II-IIIA and IIIB (T > 5 cm and N2) NSCLC, who have completed standard-of-care adjuvant treatments, including cisplatin-based chemotherapy and mediastinal radiation therapy (if applicable). Prior treatment with neoadjuvant chemotherapy or neoadjuvant radiotherapy is not permitted. Approximately 1500 pts will be randomized 1:1 to receive canakinumab (200 mg Q3W, s.c) or placebo (Q3W, s.c.) for 18 cycles or until disease recurrence, unacceptable toxicity, treatment discontinuation at the discretion of the investigator or pt, death, or loss to follow-up. Randomization will be stratified by AJCC/UICC v.8 stage, tumor histology, and region. In the amended protocol, a sub-study was included to determine the biomarker levels in the blood at pre- and post-surgery, and to establish their association with canakinumab efficacy. The primary objective is disease-free survival (per investigator assessment). Secondary objectives include overall survival (key secondary objective), lung cancer-specific survival, safety, pharmacokinetics and immunogenicity of canakinumab, and pt-reported outcomes. Enrollment is ongoing. Clinical trial identification: CACZ885T2301. Legal entity responsible for the study: Novartis. Funding: Novartis. Disclosure: B.C. Cho: Honoraria (self): Novartis, Bayer, AstraZeneca, MOGAM Institute, Dong-A ST, Champions Oncology, Janssen, Yuhan, Ono, Dizal Pharma, MSD; Advisory / Consultancy: Novartis, AstraZeneca, Boehringer Ingelheim, Roche, BMS, Ono, Yuhan, Pfizer, Eli Lilly, Janssen, Takeda, MSD; Research grant / Funding (self): Novartis, Bayer, AstraZeneca, MOGAM Institute, Dong-A ST, Champions Oncology, Janssen, Yuhan, Ono, Dizal Pharma, MSD; Shareholder / Stockholder / Stock options: TheraCanVac Inc; Licensing / Royalties: Champions Oncology . G-C. Chang: Honoraria (self): F. Hoffmann–La Roche, Ltd, Eli Lilly and Company Oncology, AstraZeneca, Pfizer, Boehringer Ingelheim, Bristol-Myers Squibb, and Merck Sharp & Dohme . Y-C. Kim: Honoraria (self): AstraZeneca, Roche, Boehringer Ingelheim; Research grant / Funding (self): AstraZeneca, Roche, Boehringer Ingelheim. S. Geater: Honoraria (self): AstraZeneca, Boehringer Ingelheim, Roche; Advisory / Consultancy: Boehringer Ingelheim; Research grant / Funding (institution): AstraZeneca, Boehringer Ingelheim, Roche, MSD; Travel / Accommodation / Expenses: AstraZeneca, Boehringer Ingelheim, Roche. S. Saeteng: Honoraria (self): AstraZeneca, Novartis : Speaker. Y. Goto: Speaker Bureau / Expert testimony: AstraZeneca, Eli Lilly, Chugai, Taiho Pharmaceutical, Boehringer Ingelheim, Ono Pharmaceutical, Bristol-Myers Squibb, Pfizer, MSD, Shionogi Pharma, Novartis; Advisory / Consultancy: Eli Lilly, Chugai, Taiho Pharmaceutical, Boehringer Ingelheim, Pfizer, Novartis, AstraZeneca, Glaxo Smith Kline; Research grant / Funding (self): AbbVie, Eli Lilly, Taiho Pharmaceutical, Bristol-Myers Squibb, Ono Pharmaceutical, Daiichi Sankyo, Pfizer, Novartis, Kyorin. S. Lu: Research grant / Funding (self): AstraZeneca, Hutchison, Roche; Advisory / Consultancy: AstraZeneca, Boehringer Ingelheim, Hutchison MediPharma, Simcere, Roche; Honoraria (self): AstraZeneca, Roche. A. Ardizzoni: Advisory / Consultancy: MDS, Roche; Honoraria (self): MSD, BMS, Pfizer, Lilly; Research grant / Funding (self): BMS, Celgene, Roche; Leadership role: Member Educational Committee. F. Barlesi: Honoraria (self): AstraZeneca, Bayer, Bristol-Myers Squibb, Boehringer Ingelheim, Eli Lilly Oncology, . P. De Marchi: Advisory / Consultancy: Roche, Bayer, Msd, BMS, Pfizer, AstraZeneca; Speaker Bureau / Expert Testimony: Roche, Bayer, MSD, BMS, Pfizer, AstraZeneca; Travel / Accommodation / Expenses: Roche, MSD, BMS, AstraZeneca . L. Paz-Ares: Advisory / Consultancy: Roche, Lilly, Novartis, Pfizer, BMS, MSD, Takeda, AstraZeneca, Boehringer Ingelheim, Bayer, Janssen, Celgene; Honoraria (self): Roche, Lilly, Novartis, Pfizer, BMS, MSD, Amgen, Merck, Sanofi, Takeda, AstraZeneca, Boehringer Ingelheim, Bayer, Janssen, PharmaMar, Celgene. D.R. Spigel: Advisory / Consultancy: AbbVie (Inst); Amgen (Inst); AstraZeneca (Inst); Boehringer Ingelheim (Inst); Bristol-Myers Squibb (Inst); Celgene (Inst); Evelo Therapeutics (Inst); Foundation Medicine (Inst); Genentech/Roche (Inst); GlaxoSmithKline (Inst); Illumina (Inst); Lilly (Inst); Research grant / Funding (institution): AbbVie (Inst); Acerta Pharma (Inst); Aeglea Biotherapeutics (Inst); Amgen (Inst); ARMO BioSciences (Inst); Astellas Pharma (Inst); AstraZeneca (Inst); Boehringer Ingelheim (Inst); Bristol-Myers Squibb (Inst); Celgene (Inst); Celldex (Inst); Clovis Oncolog; Travel / Accommodation / Expenses: AstraZeneca; Boehringer Ingelheim; Bristol-Myers Squibb; Celgene; EMD Serono; Genentech; Genzyme; Intuitive Surgical; Lilly; Merck; Pfizer; Purdue Pharma; Spectrum Pharmaceuticals; Sysmex. M. Thomas: Advisory / Consultancy: Novartis, Lilly, Pfizer, Bristol-Myers Squibb, Roche, AstraZeneca, Boehringer Ingelheim, MSD; Honoraria (self): Roche, Bristol-Myers Squibb, Lilly, AstraZeneca, Novartis, Pfizer, Boehringer Ingelheim, MSD; Research grant / Funding (self): Roche, BMS, MSD, AstraZeneca, Takeda. E.B. Garon: Advisory / Consultancy: Dracen, EMD Serono; Research grant / Funding (self): AstraZeneca, BMS, Eli Lilly, Genentech, Merck, Novartis, Neon, Iovance, Dynavax, Mirati. M. Leung: Shareholder / Stockholder / Stock options: Novartis; Full / Part-time employment: Novartis. J. Baum: Shareholder / Stockholder / Stock options: Novartis stock; Full / Part-time employment: Novartis. Spouse (Lauren Baum) – Abbot Laboratories. Z. Zewen: Full / Part-time employment: Novartis; Shareholder / Stockholder / Stock options: Novartis. B. Mookerjee: Full / Part-time employment: Novartis; Shareholder / Stockholder / Stock options: Novartis, GlaxoSmithKline, Incyte, AstraZeneca. J.C-H. Yang: Advisory / Consultancy: Boehringer Ingelheim, Eli Lilly, Bayer, Roche/Genentech, Chugai Pharmaceutical, MSD, Merck Serono, Pfizer, Novartis, Celgene, Merrimack, Yuhan Pharmaceuticals, BMS, Ono Pharmaceuticals, Daiichi-Sankyo, Hansoh Pharmaceuticals, Takeda Pharmaceuticals, Bluep; Honoraria (self): Boehringer Ingelheim, Eli Lilly, Bayer, Roche/Genentech, Chugai Pharmaceutical, MSD, Merck Serono, Pfizer, Novartis, Celgene, Merrimack, Yuhan Pharmaceuticals, BMS, Ono Pharmaceuticals, Daiichi-Sankyo, Hansoh Pharmaceuticals, Takeda Pharmaceuticals, Bluep; Leadership role: IASLC CME activity: Author/Board of Directors/Presenter/Reviewer. All other authors have declared no conflicts of interest.